(untitled) (Journal of the Bangladesh Agricultural University, 2018)
The landmark-based morphometric and meristic analysis of three different stocks from the Atrai, the Jamuna and the Kangsha of Bhagna (Labeo ariza, Hamilton 1807) were examined from a phenotypical point of view to evaluate the population structure and to assess shape variation. A total of 90 Bhagna (L. ariza) were collected from three different water bodies: the Atrai, the Jamuna and the Kangsha of Bangladesh during January, 2017. Ten morphometric and nine meristic characters were analyzed along with twenty-two truss network measurements. One way ANOVA showed that all morphometric, meristic and truss network measurement were significantly different (P<0.001) among three different stock of the fish. For morphometric and landmark measurements, the first discriminant functions (DF) accounted for 98.6% and 97.9% and the second DF accounted for 1.4% and 2.1%, respectively among group variability, explaining 100% of total among groups variability. For the morphometric and truss network measurements, plotting discriminant functions showed a well-separated clusters of the stocks indicating that the measurement were significantly different among three stocks. The dendrogram based on morphometric and landmark distances data showed two major clusters; the Atrai and Jamuna stocks in one cluster and the Kangsha stock in another cluster. High degree of variation was observed in morphological characteristics among three different stocks (the Atrai, Jamuna and Kangsha) of L .ariza due to their environmental variation and separate geographical location. The results of this study are very useful for proper conservation and successful management of L. ariza and also for the scientific community for the further research. J. Bangladesh Agril. Univ. 16(1): 164-170, April 2018